Dermoid Cyst of the Infratemporal Fossa: Case Report and Review of the Literature - Triplett, Thomas M.; Griffith, Adam; Hatanpaa, Kimmo J.; Barnett, Samuel L. (Journal of Neurological Surgery Reports, 2014)
Background Intracranial dermoid cysts are rare tumors of congenital origin. We report a case of a large dermoid tumor arising in the infratemporal fossa (ITF) with erosion into the middle cranial fossa. After reviewing the literature, we believe this represents the first reported dermoid tumor of the ITF with extension into the middle cranial fossa.Results A 21-year-old women presented with a large cystic mass involving the left infratemporal fossa and middle cranial fossa that was discovered following a motor vehicle collision. Neurologic examination was normal. The mass was resected through a frontotemporal extradural approach with endoscopic assistance. Imaging studies, gross findings, and histopathology were consistent with a dermoid tumor.Conclusion This is the first report of a dermoid cyst arising in the ITF with extension into the middle cranial fossa. We suggest including dermoid tumor in the differential diagnosis of cystic abnormalities in this region. Complete resection of the cyst remains the preferred treatment with surgical approach guided by preoperative imaging.
Keywords: dermoid; cyst; infratemporal; middle fossa